How Burman privilege excludes the Rohingya from the contemporary Myanmar society - Trilho, Tatiana Andreia Mota Pires de Aguiar (2021)
Myanmar is a country located in Southeast Asia that in 2017 and 2018 was worthy of international attention, due to accusations of genocide and ethnic cleansing directed at the country's military that were involved in the episodes of violence that led hundreds of thousands of Rohingya to fleeing the country and seeking refuge in Bangladesh. The internal reluctance to condemn the military for acts of excessive and disproportionate violence led to the removal of Aung San Suu Kyi – the country's de facto leader and former Nobel Peace Prize laureate – from Nobel Prize itself. In this context, it is important to understand the reason behind the legitimization of these violent acts in the eyes of the general population of Myanmar who consider the Rohingya to be illegal immigrants from Bangladesh, calling them Bengalis and refusing to recognize the Rohingya identity with which identify themselves. It is possible to understand that in a country where ethnicity is related to the obtaining (or not) any type of power that the dominant ethnic group, the Burmans, have a legitimacy and privilege that other ethnic minorities do not enjoy. Against this background, it is pertinent to investigate to what extent the Burman privilege not only excludes the Rohingya but also legitimizes the discriminatory behavior and treatment that the community has been subjected to in the country.